2017
DOI: 10.1111/1758-5899.12409
|View full text |Cite
|
Sign up to set email alerts
|

How Do Domestic Regulatory Traditions Shape CSR in Large International US and UK Firms?

Abstract: This article examines corporate social responsibility (CSR) pertaining to labor standards in apparel and tax transparency in extractives and explores how domestic regulatory traditions shape CSR in large international US and UK firms. Reflecting their more collaborative business‐government traditions, British firms are more willing to join international CSR multi‐stakeholder initiatives with business‐critical actors such as unions and civil society actors. The US has a more top‐down regulatory approach, which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 55 publications
(90 reference statements)
0
11
0
Order By: Relevance
“…Finally, this study has focused on government mandatory and supportive international CSR initiatives but does not consider the impact on firm‐level CSR initiatives in UK and US corporations. It is to be expected that national institutions may exert a substantial influence over firms’ international CSR strategies (Christopherson and Lillie ; Knudsen ; Lane ).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, this study has focused on government mandatory and supportive international CSR initiatives but does not consider the impact on firm‐level CSR initiatives in UK and US corporations. It is to be expected that national institutions may exert a substantial influence over firms’ international CSR strategies (Christopherson and Lillie ; Knudsen ; Lane ).…”
Section: Discussionmentioning
confidence: 99%
“…In our study, we identified 21 industry application categories. While the instruments applicable to any or multiple industries are not the most common in Raynolds et al ’s (2014) study, it is a finding that is reflected by the instruments included in Knudsen’s (2017) study. In this study, a large difference in the coverage of the instruments between IGOs and INGOs was identified.…”
Section: Discussionmentioning
confidence: 98%
“…ICSRIs can be distinguished according to the industry sectors to which they are applicable (Fransen et al , 2019; Knudsen, 2017; Perez et al , 2019). These can be broad, such as the extractive and garment industries (Knudsen, 2017), or specific, such as the tea and flower industries (Fransen et al , 2019). Moreover, some schemes may be applicable to multiple, and even all, industry sectors (Perez et al , 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations